2010
DOI: 10.1016/j.cub.2010.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Targeting of Bazooka/PAR-3 Is Mediated by Direct Binding to Phosphoinositide Lipids

Abstract: Cell polarity in higher animals is controlled by evolutionarily conserved protein complexes, which localize to the cytocortex in a polarized manner. The PAR-3/PAR-6/atypical protein kinase C (aPKC) complex is the first to become asymmetrically localized, and it controls the localization of additional complexes functioning further downstream in the regulation of cell polarity. The first component of the PAR-3/PAR-6/aPKC complex that is localized to the cortex is Bazooka/PAR-3 (Baz), a large scaffolding protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(154 citation statements)
references
References 36 publications
6
146
0
2
Order By: Relevance
“…Drosophila Genetics-The following mutant alleles were used: PATJ ⌬1 (21), baz (30,31), baz XR11 (32), sdt K85 (33), and crb 11A22 (34). Germ line clones were generated with the mutant alleles recombined with FRT using the dominant female sterile technique (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila Genetics-The following mutant alleles were used: PATJ ⌬1 (21), baz (30,31), baz XR11 (32), sdt K85 (33), and crb 11A22 (34). Germ line clones were generated with the mutant alleles recombined with FRT using the dominant female sterile technique (35).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a protein composed of the three PDZ domains of PATJ and a fragment of Baz that accumulates at the apical junctions by direct binding to the plasma membrane (31), is, to a large extent, correctly targeted to the apical junctions (PATJ ⌬L27 -LB(Baz) , Fig. 5D) but does not rescue the PATJ null allele (Fig.…”
Section: Association With Both Crb-sdt and Baz-sdt Complexes Rather Tmentioning
confidence: 99%
“…Additional work shows that the interaction between PAR-3 and PTEN was conserved in mammals and necessary for the establishment of epithelial polarity (Feng et al 2008). Interestingly, two recent studies have reported that Baz/PAR-3 can bind directly to PIs in flies and mammals (Wu et al 2007;Krahn et al 2010). There is a PIs specify membrane identity in epithelial cells.…”
Section: Phosphoinositides In Cell Architecturementioning
confidence: 99%
“…From genetic studies on Drosophila ectoderm and mammalian culture cells, it appears that at least four spatially restricted membrane associated protein-scaffolds are required for regulating the maturation of the ZA in epithelial cells: the PAR-3-PAR-6-aPKC (PPC) complex, the Crumbs-Stardust-Patj complex, the Scribble-Dlg-Lgl complex, and the YurtCoracle group (Betschinger et al, 2003;Bilder et al, 2003;Harris and Peifer, 2005;Harris and Peifer, 2007;Krahn et al, 2010a;Krahn et al, 2010b;Laprise et al, 2009;Plant et al, 2003;Tanentzapf and Tepass, 2003;Yamanaka et al, 2003).…”
Section: Apicobasal Polarity Complexes In the C Elegans Intestinementioning
confidence: 99%
“…In Drosophila membrane targeting of Bazooka/PAR-3 is mediated by direct binding to phosphoinositide lipids (Krahn et al, 2010b). Recent deletion and point mutation analyses of three LAP proteins, using C. elegans LET-413, human Erbin and human Scribble demonstrate that their LRR domain is crucial for membrane targeting (Legouis et al, 2003).…”
Section: Targeting Of Junctional Complexesmentioning
confidence: 99%